Pengaruh Budaya Organisasi, Beban Kerja, Dan Target Kerja Terhadap Kinerja Pegawai Pada Industri Perbankan - Rizka Octaviani; Yuni Pratikno; Bambang Nurakhim (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study aims to examine and analyze the influence of organizational culture, workload, and work targets, both partially and simultaneously, on employee performance in the banking industry. The research approach used was a quantitative explanatory survey method. The population in this study included all banking industry employees in the study area. The sample size was determined using the Slovin formula, resulting in a sample of 42 respondents selected through simple random sampling. Data collection was conducted using a structured questionnaire with a 5-point Likert scale that has been tested for validity and reliability. The data analysis techniques used in this study were multiple linear regression analysis, the F-test (simultaneous), the t-test (partial), and the coefficient of determination (R²) analysis using SPSS. The results indicate that, partially, organizational culture has a positive and significant influence on employee performance. Workload significantly influences performance, where an optimal workload can boost productivity, but an excessive workload has the potential to reduce effectiveness. Work targets also proved to have a positive and significant influence on employee performance through clear achievement indicators. Simultaneously, the ANOVA test results showed an F-value of 30.605 with a significance level of 0.000 (<0.05), indicating that organizational culture, workload, and work targets jointly have a significant influence on employee performance. The R-square value obtained was 0.707, indicating that 70.7% of the variation in employee performance can be explained by these three independent variables, while the remaining 29.3% is explained by factors outside this research model. Banking management is advised to periodically evaluate workload distribution and set realistic targets to maintain stable performance and employee well-being.